Effectiveness of narrative nursing on depression patients with suicide attempt: A preliminary randomized controlled trial - Liu Junyu; Luo Yuan; Wang Jianjian, RN; Zhang Zhanchou; Zhao Liping (Acta Psychologica)
Background and objectives: Suicidal behavior, encompassing both suicidal ideation and attempts, is a common symptom among individuals with depression, significantly contributing to the overall burden of the illness. This study aimed to develop a narrative nursing method based on the Three-Step Theory of Suicide and applied this method to explore its preliminary effectiveness in depression patients with suicide attempts. Methods: 50 patients with depression and high suicide ideation were randomly allocated to two groups: an intervention group, which received narrative nursing based on the Three-Step Theory of Suicide alongside usual nursing, and a control group, which received only usual nursing. The differences in depression levels, drug attitudes, and suicidal ideation were compared between the two groups both before and after the intervention. This study has been officially registered in the China Clinical Trial Registry (Registration No. ChiCTR2300079100). Results: A total of 50 patients were enrolled in this study, with 25 patients in the intervention group and 25 patients in the control group. 6 participants were lost to follow-up in the intervention group, and 4 participants were lost to follow-up in the control group. After the intervention, the intervention group showed significant effectiveness compared to the control group in the score of depression, drug attitude and idea of suicide. Conclusions: Narrative nursing base on Three-Step Theory of Suicide could relieve depression, improve drug attitudes, thereby enhancing medication and treatment adherence, and alleviate suicidal ideation. Therefore, the method could be further applied to explore long-term effects.